Analisis Teks Koran Online Terhadap Pemahaman Membaca Inferensial Mahasiswa Tehnik Informatika di Surakarta - Marginingsih; Chandra Halim (Politeknosains, 2018)
The purpose of this research is to analyze the profile of inferensial reading comprehension text of online newspaper students of Informatics Engineering Study Program STMIK Duta Bangsa Surakarta and STMIK Sinar Nusantara. Understanding of student inferential reading is seen based on two indicators namely finding the main idea that is not written in the text and find implied information. In this study, researchers used three levels of reading comprehension. Values above 60% are categorized independent, 40-60 are categorized as intructional levels, and values below 40 are categorized as frustrating. Data analysis includes validity and reliability test instrument multiple choice. After the results of the analysis of the problem is valid and reliable, the instrument is tested to the respondent to know the average result of the students score of each indicator of inferential reading comprehension. The result of research shows that the average result of the students of Informatics Engineering STMIK Duta Bangsa in finding the main idea is 36.1%, while STMIK Sinar Nusantara student is 34.4%. The average result of students STMIK Duta Bangsa in finding implied information is 37%, whereas STMIK Sinar Nusantara student is 32.9%. From these results students need to be given more reading practice inferential comprehension in the learning process.